Study on the performance of C-band erbium doped fiber amplifier / Sazreena Saribudin - Saribudin, Sazreena (2015)
This work analyzed the performance of erbium doped fiber amplifier (EDFA) using different EDF length and pump power. In this study, an EDFA simulation program has been written in Matlab to analyze the active fiber length in around 3m, 15m, 20m, 50m, 80m and 100m to characterize the Gain, ASE power and amplifier output power versus fiber length and input signal power variations of a forward pumping and backward pumping. These EDFA operating in C band (1525-1565 nm) as functions of Er3+ fiber length, injected pump power, signal input power and Er3+ doping density. The program solves the rate and propagation equations numerically and shows the results graphically. Thus, Gain and ASE performance of an EDFA given with its physical parameters can be graphically obtained and the required physical parameters of an EDFA with desired operating performance can be easily optimized.